2022
DOI: 10.34172/jech.2022.a-10-1015-2
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Anabolic Steroids Use in Bodybuilding Athletes Based on the Theory of Planned Behavior

Abstract: Background: Athletes’ use of androgenic-anabolic steroids (AASs) is a significant health problem. This study aimed to determine factors associated with AAS in male bodybuilders by applying the theory of planned behavior (TPB). Methods: Using a multistage random sampling procedure, this descriptive-analytical cross-sectional study was performed on 429 athletes participating in gyms in Qom, Iran, in 2019. The data collection tool was a questionnaire, including demographic information and questions related to TPB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
2
1
0
Order By: Relevance
“…Consistent with the current study, previous research (31,37) reported that PBC was the strongest predictor of organ donation intention, suggesting that participants believed in their personal control and ability to donate organs. Conversely, in the study of Khoshravesh et al, the PBC construct did not predict signing the donor card directly (11).…”
Section: Perceived Behavioral Control and Intention To Donate Organssupporting
confidence: 90%
See 1 more Smart Citation
“…Consistent with the current study, previous research (31,37) reported that PBC was the strongest predictor of organ donation intention, suggesting that participants believed in their personal control and ability to donate organs. Conversely, in the study of Khoshravesh et al, the PBC construct did not predict signing the donor card directly (11).…”
Section: Perceived Behavioral Control and Intention To Donate Organssupporting
confidence: 90%
“…According to the results of the path analysis of model fit, the path coefficient related to PBC and attitude toward behavioral intention to donate organs was statistically significant. The concept of PBC contributes more to predicting organ donation intention, which conforms to the results of some studies (26,37).…”
Section: Perceived Behavioral Control and Intention To Donate Organssupporting
confidence: 85%
“…45,46 Previous studies suggest that attitude and self-control affect a person's decision to wear a helmet and drive safely, which involves the psychological dynamics of obeying predetermined traffic laws. 47 The waste problem requires more attention from various parties, both the government and the surrounding community. Until now, the problem of waste has not been resolved.…”
Section: Discussionmentioning
confidence: 99%